α-Pinene Enhances the Anticancer Activity of Natural Killer Cells via ERK/AKT Pathway - Jo, Hantae (Int J Mol Sci, 2021)
Natural killer (NK) cells are lymphocytes that can directly destroy cancer cells. When NK cells are activated, CD56 and CD107a markers are able to recognize cancer cells and release perforin and granzyme B proteins that induce apoptosis in the targeted cells. In this study, we focused on the role of phytoncides in activating NK cells and promoting anticancer effects. We tested the effects of several phytoncide compounds on NK-92mi cells and demonstrated that α-pinene treatment exhibited higher anticancer effects, as observed by the increased levels of perforin, granzyme B, CD56 and CD107a. Furthermore, α-pinene treatment in NK-92mi cells increased NK cell cytotoxicity in two different cell lines, and immunoblot assays revealed that the ERK/AKT pathway is involved in NK cell cytotoxicity in response to phytoncides. Furthermore, CT-26 colon cancer cells were allografted subcutaneously into BALB/c mice, and α-pinene treatment then inhibited allografted tumor growth. Our findings demonstrate that α-pinene activates NK cells and increases NK cell cytotoxicity, suggesting it is a potential compound for cancer immunotherapy.